Ảnh hưởng của đặc điểm công ty đến sự điều chỉnh lợi nhuận sau kiểm toán: Trường hợp các công ty niêm yết tại Việt Nam - Nguyen , Viet; Nguyen Van , Huong (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This study aims to examine the effects of firm characteristics on misstatements of profit shown in the income statements which must be adjusted after auditing of Vietnamese listed firms. Using a sample of 2,490 annual financial statements collected for the period from 2010 to 2015 and logistic regression method, we find evidence of the characteristics of firms such as losses in the previous year, previous annual misstatements, current earning pressure, ratio of debt, and market values versus book values which impact the likelihood of profit misinterpretation and adjustment after the release of audit results. These findings provide a basis for financial statement users’ identification of misstatements of target firms for sensible economic decisions.
Keywords: Firm characteristics; Losses in the previous year; Earning pressure; Previous annual misstatements; Profit adjustment